Breaking down and building up: metáforas conceituais e ensino/aprendizagem de verbos de duas ou mais palavras - Hodgson, Elaine Carvalho Chaves (2010)
This study proposes application of the principles of Conceptual Metaphor Theory (CMT), put forward by Lakoff and Johnson, to the teaching/learning of English as a foreign language (EFL), specifically the teaching/learning of verbs of two or more words, commonly known as phrasal verbs. The relationship between conceptual metaphor and cognition is analysed, particularly between conceptual metaphors related to the particles up and down, the main focus of this research, and seeks to explain how this relationship may influence our language and how we understand and use this kind of verb. The study both revises and explores the meanings of these particles with a view to establish a relation between conceptual metaphor and the meaning of verbs of two or more words. The investigative method adopted is that of experimental research. Thus, in order to enable a broader analysis of the data, a mixed approach is used, which includes a pre- and post-test, a tool more related to experimental research, but also makes use of notes made by the researcher during application of exercises to the control group and the experimental group, following the example of similar studies which seek a broader view of both the product and the process of teaching/learning. Teaching procedures which make us of conceptual metaphors as a tool facilitating learning/teaching of phrasal verbs are suggested, as the latter are very common in English, but are considered complicated or even impossible to learn by Portuguese-speaking learners and teachers of English as a Foreign Language. Despite the fact that statistical results failed to show evidence that the teaching of phrasal verbs is more efficient than traditional teaching, the qualitative results point to the fact that CMT may have a highly positive contribution to make to the teaching of English as a Foreign Language.